Penggunaan Biopolimer Polikaprolakton Sebagai Matrik Herbisida Lepas Lambat Asam 2,4-Diklorofenoksi Asetat - Akmal Djamaan; Maria Ulfa; Netty Suharti (Jurnal Farmasi Higea, 2012)
The formulation of microcapsule of 2,4-dichlorophenoxy acetate acid using biopolymer polycaprolactone as a matrix using solvent evaporation method has been carried out. The microcapsule formula was used three types with the ratio 2:1, 1:1, 1:2 between 2,4-dichlorophenoxy acetate acid and polycaprolactone. Distribution particle test was used calibrated microscope. Active substance release test was detected by UV-Vis spectrophotometer. Polycaprolactone can be used as the matrix polymer for slow release preparations and influence to the release of active substance 2,4-dichlorophenoxyacetate acid. Result showed that recovery test of the formula-2 containing 86.5 % higher than formula-1, 84.5% and formula-3 78.2%. Model of the kinetics of the release active substance from microcapsule which correlation coefficient close to one is formula-1 which follow zero order kinetics.